Implementasi Strategi Customer Relationship Management (CRM) Pada PT PLN (Persero) UP3 Surabaya Barat - Regita Bintari Prameswari; Jojok Dwiridotjahjono (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Customer Relationship Management (CRM) is a crucial strategy in strengthening relationships with customers and improving service quality. This research examines the implementation of CRM at PT PLN (Persero) UP3 West Surabaya, which aims to improve the efficiency of collecting and analyzing customer data through the use of application technology and websites. By understanding customer characteristics, behavior, and needs through effective profiling, PT PLN (Persero) UP3 West Surabaya can develop a more personalized and responsive CRM strategy, and improve ongoing interaction with customers. This research uses observation method and qualitative approach with literature review method to examine CRM implementation at PT PLN (Persero) UP3 West Surabaya. The results showed that the use of a customer profiling database can help PT PLN in creating a better customer experience and increasing customer loyalty. Successful CRM implementation requires careful planning, adequate technology, and support from all parties in the organization.